Efficacy of attention bias modification training for depressed adults: a randomized clinical trial. Issue 16 (26th December 2022) - Hsu, Kean J.; Shumake, Jason; Caffey, Kayla; Risom, Semeon; Labrada, Jocelyn; Smits, Jasper A. J.; Schnyer, David M.; Beevers, Christopher G.
Abstract: Background: This study examined the efficacy of attention bias modification training (ABMT) for the treatment of depression. Methods: In this randomized clinical trial, 145 adults (77% female, 62% white) with at least moderate depression severity [i.e. self-reported Quick Inventory of Depressive Symptomatology (QIDS-SR) ⩾13] and a negative attention bias were randomized to active ABMT, sham ABMT, or assessments only. The training consisted of two in-clinic and three (brief) at-home ABMT sessions per week for 4 weeks (2224 training trials total). The pre-registered primary outcome was change in QIDS-SR. Secondary outcomes were the 17-item Hamilton Depression Rating Scale (HRSD) and anhedonic depression and anxious arousal from the Mood and Anxiety Symptom Questionnaire (MASQ). Primary and secondary outcomes were administered at baseline and four weekly assessments during ABMT. Results: Intent-to-treat analyses indicated that, relative to assessment-only, active ABMT significantly reduced QIDS-SR and HRSD scores by an additional 0.62 ± 0.23 ( p = 0.008, d = −0.57) and 0.74 ± 0.31 ( p = 0.021, d = −0.49) points per week. Similar results were observed for active v. sham ABMT: a greater symptom reduction of 0.44 ± 0.24 QIDS-SR ( p = 0.067, d = −0.41) and 0.69 ± 0.32 HRSD ( p = 0.033, d = −0.42) points per week. Sham ABMT did not significantly differ from the assessment-only condition. No significant differences were observed for the MASQ scales. Conclusion: Depressed individuals with at least modest negative attentional bias benefitted from active ABMT.